The Board Composition as an Explanatory Factor of the Capital Structure of Mexican Listed Companies - Puente Esparza, Martha Luisa; Briano-Turrent, Guadalupe del Carmen; Garca-Estrada, Luis ngel (Universitas Syiah Kuala, 2018)
Objective The objective of this study is to analyze the influence of the composition of the BD on the leverage level in companies listed on the Mexican Stock Exchange (MSE) in the materials and industrial sectors during the 2009-2013 period. Particularly, we study four dimensions of the board: size, independence, female presence and the COB-CEO duality.Design/methodology This study focused on the materials and industrial comprising about 50% of all listed companies on the Mexican Stock Exchange. The sample consists of 48 companies and 207 year-observations corresponding to the 2009-2013 period. Using a multiple regression analysis. This study is a pioneer in analyzing these variables in Mexico, since previous literature has focused on developed and Anglo-Saxon countries.Results The results show that size and independence of the board affect the leverage level. In addition, certain business characteristics such as the industrial sector, the companys age, profitability and size influence the leverage level in Mexican listed companies. The results provide practical evidence for those responsible for issuing policies and principles of corporate governance as well as for the companies under analysis.Research limitations There are several limitations in this study. In the first place, only two sectors of the companies listed in Mexico during the 2009-2013 period were analyzed. On the other hand, linear regression analysis was used, which does not solve the problems of causality between variables, however we did not count with enough observations. However, despite the limitations mentioned, the results are interesting in the case of Mexico. In addition, this study can be extended in the future for other sectors and extend the period of analysis, as well as include other Latin American countries to carry out comparative studies.Keywords Board of Directors, Leverage, Corporate Governance, Mexico